Affordances and the musically extended mind - Krueger, Joel (Frontiers in Psychology, 2014)
I defend a model of the musically extended mind. I consider how acts of “musicking” grant access to novel emotional experiences otherwise inaccessible. First, I discuss the idea of “musical affordances” and specify both what musical affordances are and how they invite different forms of entrainment. Next, I argue that musical affordances—via soliciting different forms of entrainment—enhance the functionality of various endogenous, emotion-granting regulative processes, drawing novel experiences out of us with an expanded complexity and phenomenal character. I suggest that music therefore ought to be thought of as part of the vehicle needed to realize these emotional experiences. I appeal to different sources of empirical work to develop this idea.